Moderating Effect of Board Diversity on the Relationship between Environmental, Social, and Governance Disclosure Quality and Value of Listed Industrial Goods Companies in Nigeria - Yusuf Mohammed Muktar; Mohammed Musa Naburgi; Musa Umar Doshiro (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2025)
The study examined the moderating effect of board diversity on the relationship between Environmental, Social, and Governance (ESG) disclosure quality and the value of listed industrial goods companies in Nigeria. In recent years, ESG considerations have emerged as critical determinants of corporate reputation, investor confidence, and financial performance globally. While ESG disclosures provide non-financial information that informs stakeholders about a firm’s sustainability practices, the quality of these disclosures varies widely across firms and sectors. Corporate governance, particularly board diversity, is theorized to influence the effectiveness of ESG reporting by bringing multiple perspectives, enhancing oversight, and promoting transparency. Using a panel dataset of 13 industrial goods firms listed on the Nigerian Exchange between 2015 and 2024, this study employs multiple regression and moderation analysis to examine how board diversity affects the link between ESG disclosure quality and firm value, proxied by market capitalization and Tobin’s Q. Preliminary findings indicate that high-quality ESG disclosure is positively associated with firm value, but the strength of this relationship is significantly enhanced when boards are diverse in terms of gender, expertise, and tenure. The results suggest that board diversity acts as a critical governance mechanism that amplifies the market benefits of robust ESG practices. This study contributes to the growing literature on corporate sustainability in emerging markets by highlighting the importance of integrating governance and ESG strategies to maximize firm value. It also offers practical implications for policymakers, regulators, and corporate boards aiming to strengthen ESG reporting frameworks and promote sustainable business practices in Nigeria.